Pengaruh Celebrity Endorser, Efektivitas Iklan, dan Word Of Mouth Terhadap Minat Beli Konsumen Online Shop (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Tanjungpura) - admin, JONATHAN RENADO B11112149 (Jurnal Manajemen Update, 2016)
This study was conducted to determine whether Celebrity Endorser, Effectivity of Advertising, and Word of Mouth positively affected towards the online shop consumer Purchase Intentions. This study has conducted at Faculty of Economics and Business University Tanjungpura with 100 respondents through obtained purposive sampling technique. This study has used SPSS version 17 to analyse and determine the profile of respondent toward variation ofÂ  each research variable indicators. The method used in this study is multiple linear regression. The result stated that Celebrity Endorser has positively affected and significantly affected the consumer purchase intention, Effectivity of Advertising has positively affected and significantly affected the consumer purchase intention, Word of Mouth has positively affected and significantly affected the consumer purchase intention Keywords : Celebrity Endorser, Effectivity of Advertising, Word Of Mouth, Consumer Puchace Intentons